2016
DOI: 10.21103/article6(3)_oa15
|View full text |Cite
|
Sign up to set email alerts
|

7-(1-Methyl-3-Pyrrolyl-)-4,6-Dinitrobenzofuroxan Reduces the Frequency of Antibiotic Resistance Mutations Induced by Ciprofloxacin in Bacteria

Abstract: The aim of the present study was to investigate biological properties of the novel nitrobenzoxadiazole derivative 7-(1-methyl-3-pyrrolyl-)-4,6-dinitrobenzofuroxan. Materials and Methods:We used a bioluminescent test based on a set of lux-biosensors, which are genetically modified E.coli strains able to react on different types of factors that can induce an SOS-response with light emission. The spontaneous and induced mutation frequencies of antibiotic resistance in E. coli were determined by methods of classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…It is shown that SOS-deficient strains adapt more slowly to antibiotics [ 3 ]. Furthermore, as has been shown in our studies [ 4 ], activation of the SOS response by one therapeutic agent can lead to acquiring resistance to another.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…It is shown that SOS-deficient strains adapt more slowly to antibiotics [ 3 ]. Furthermore, as has been shown in our studies [ 4 ], activation of the SOS response by one therapeutic agent can lead to acquiring resistance to another.…”
Section: Introductionsupporting
confidence: 64%
“…Previously, we used this method to estimate the DNA-protective and antioxidant activity of bacterial fermentates [ 14 ]. Additionally, the SOS-inhibitory activity of a novel synthetic compound, nitrobenzoxadiazole derivative, 7-(1-methyl-3-pyrrolyl-)-4,6-dinitrobenzofuroxan, was shown in one of our works [ 4 ].…”
Section: Introductionmentioning
confidence: 99%